Spoznajmo prsti okoli nas - Vovk Korže, Ana (Geografski obzornik, 2006)
Already in the past, human beings have been interested in the soil characteristics - mainly due to speculations regarding harvest. Nowadays, there are many accessories and methods for soil research; the very basic are presented.
Keywords: pedogeografija; prst (pedologija); tla; tipi; terensko delo